Permasalahan perilaku kurangnya minat belajar bahasa Inggris siswa-siswi di MTsN 7 Malang: Studi kasus di Desa Pandanajeng Kecamatan Tumpang Kabupaten Malang - Roziqin, Muhammad (Maliki Interdisciplinary Journal, 2024)
The waning enthusiasm of students towards learning the English language has had a broad impact on the world of education in the current modern era, especially as the generation of sons and daughters of this country are faced with various challenges from abroad and within the country, and we cannot deny the high level of digital development and very massive technology. So, the need for superior human resources who have insight into science is a goal that must be intensified again in order to achieve a developed country, especially in the field of education. However, as a result of the low level of awareness of students regarding the importance of learning English, it has a negative impact, even though the demands of today are related to the importance of learning English, which is an international language that is recognized throughout the world today, which has a big influence on language. Female students are required to know the basics of English to prepare themselves when in another country. The role of the environment and all supporting aspects is of course very much needed to provide a new atmosphere to increase students’ interest in learning English again so that the level of awareness in learning English increases drastically. It is hoped that the aim of this research is to provide a good solution in increasing interest in learning English for MTsN 7 Malang students located in Pandanajeng Village, Tumpang District, Malang Regency. This research is qualitative research with the type of research used, namely the case study method. The data collection techniques used in this research were observation and interviews by going directly into the field to observe the interest in learning English of MTsN 7 Malang students and conducting interviews with informants to find out the causes that influence the low level of interest in learning English of MTsN 7 students. Poor. The object of this research is the activities carried out by several MTsN 7 Malang students with problems causing the students’ lack of interest in learning English. The research results show that there are several factors that cause behavioral problems of lack of interest in learning English at MTsN 7 Malang. These factors include: gadgets, Uninteresting teaching methods, Lack of Environmental Support, and also Social Environment.